Comparison of in vitro activities of meropenem productions on Klebsiella pneumoniae isolated from hospitalized patients - Akhi, Mohammad Taghi; Asghari, Babak; Nahaei, Mohammed Reza; Memar, Mohammad Yousef; Lari, Abdolaziz Rastegar; Naghili, Behrooz; Pirzadeh, Tahereh (German Medical Science GMS Publishing House, 2014)
[english] Purpose: Antimicrobial activities of meropenem products on isolates were determined. Methods: 212 non-duplicated isolates were examined for meropenem susceptibility test by using the following disks, which were made from Meronem (AstraZeneca, UK), Exipenem (Exir, Iran) and Meroxan (DAANA, Iran) powders. MICand MICfor meropenem antibiotics were determined.Results: Meronem had good activities against most isolates of , and only a few strains had a rather high MIC. Exipenem and Meroxan showed a similar activity with Meronem. Conclusion: Regarding the comparison of two internal generic meropenem products with the external Meronem product have shown that they are equivalents in terms of microbiological activity, as measured using the disk diffusion and MIC. In developing countries, we suggested preparing disks with antibiotic powders that can be an equivalent function in microbiological activity with standard disks. In addition, since it demonstrated significant antimicrobial activity against the . For use of Exipenem and Meroxan , it would be better to perform additional testing (activity against different species, stability etc.).